(untitled) (Journal of Applied Membrane Science & Technology, 2021)
Membrane technology is cost effective solution for CO2 removal from natural gas. However, there is challenges during its application depending on the polymer material characteristic. Understanding on the polymer fundamental and transport properties, will enable proper design of pre-treatment and operating conditions that suits its capability envelope. Diffusivity selective membrane favors high pressure and high temperature conditions and vice versa for solubility selective polymer. On top of that, the robustness and durability of the resultant membrane, need to be evaluated with multicomponent mixture to understand the effect of competitive sorption, plasticization and aging phenomena that will seriously impacting the membrane performance during its application.